2022
DOI: 10.1111/evo.14647
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary loss of shell pigmentation, pattern, and eye structure in deep‐sea snails in the dysphotic zone

Abstract: Adaptations to habitats lacking light, such as the reduction or loss of eyes and pigmentation, have fascinated biologists for centuries, yet have rarely been studied in the deep sea, the earth's oldest and largest light‐limited habitat. Here, we investigate the evolutionary loss of shell pigmentation, pattern, and eye structure across a family of deep‐sea gastropods (Solariellidae). We show that within our phylogenetic framework, loss of these traits evolves without reversal, at different rates (faster for she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…nov. superficially resembles that of some brown-spotted species of Bathymophila (Williams et al 2020: fig. 7g), which Williams et al (2022) have shown belong to an undescribed Bathymophila-like genus. These differ from K. monticola in having a patent umbilicus with a heavy flange around the umbilicus, and a less acutely pointed apex.…”
Section: Paratypesmentioning
confidence: 99%
“…nov. superficially resembles that of some brown-spotted species of Bathymophila (Williams et al 2020: fig. 7g), which Williams et al (2022) have shown belong to an undescribed Bathymophila-like genus. These differ from K. monticola in having a patent umbilicus with a heavy flange around the umbilicus, and a less acutely pointed apex.…”
Section: Paratypesmentioning
confidence: 99%
“…Raw reads were adapter trimmed and quality filtered with fastp (S. Chen et al, 2018) and mapped to the human reference genome (NCBI GRCh38.p14) using bwa mem (Li, 2013) and the number of mapped reads quantified with samtools (Li et al, 2009). (Williams et al 2020(Williams et al , 2022. Inverted commas around generic names indicates uncertainty about generic assignment based on this or previous studies.…”
Section: Human Contaminationmentioning
confidence: 99%
“…Many member species are rare, and as a family they are poorly represented in museum collections worldwide, with few live-collected specimens: many species are known only from a single, dry and often damaged shell (Williams et al, 2020). Although solariellid gastropods have been the focus of previous molecular phylogenetic studies (Sumner-Rooney et al, 2016;Williams et al, 2013Williams et al, , 2022, these studies have relied on partial sequence from only four genes, which have not fully resolved relationships among genera. As such, our understanding of solariellid evolution would greatly benefit from increasing the number of gene sequences used, furthermore there are no published reference genomes for the group with limited sequence data on public databases.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, nocturnal activity is known to be associated with cellular-level adaptations such as longer rhabdoms, which also increase sensitivity (Blest and Land 1977; Narendra et al 2017). Overall, however, there has been limited research on evolutionary relationships between light quantity and quality and eye size of marine invertebrates, and particularly in deep-sea taxa due to sampling difficulties (Hiller-Adams and Case 1988; Williams et al 2022). Therefore, the accumulated material in museum collections, and their associated data, provide important opportunities for such studies, as has been demonstrated in other groups (Juarez et al 2019; Thomas et al 2020).…”
mentioning
confidence: 99%
“…Therefore, at 200 m the intensity of light available for vision has declined by over three log units (Jerlov 1976). Animals inhabiting such low-light conditions often have larger eye sizes and aperture widths which increase sensitivity (Warrant et al 2003; Warrant and Locket 2004), although the reverse trend is typically seen below 1,000 m depth where the only source of light is bioluminescence (Martin et al 2007; Liu et al 2012; Caves et al 2017; Williams et al 2022). Similarly, nocturnal activity is known to be associated with cellular-level adaptations such as longer rhabdoms, which also increase sensitivity (Blest and Land 1977; Narendra et al 2017).…”
mentioning
confidence: 99%